SOSIALISASI DAN PEMBUATAN PUPUK VERMIKOMPOS BERBAHAN DASAR TANDAN KOSONG KELAPA SAWIT (TKKS) DI KELURAHAN SUNGAI PAGAR, KABUPATEN KAMPAR, RIAU - Nursiani Lubis; Idwar Idwar; Irfandri Irfandri; Erlida Ariani; Gusmawartati Gusmawartati (LPPM Universitas Andalas, 2025)
Oil palm is a plantation commodity that plays a strategic role in the economic development of Kampar Regency. Sungai Pagar Sub-district, located in Kampar Kiri Hilir District, Kampar Regency, Riau Province, is an area where the majority of the population works as oil palm farmers. Cultivation activities in managing oil palm plantations are accompanied by an abundance of palm oil waste, particularly Empty Fruit Bunches (EFB). This waste is often considered an environmental problem due to its large volume and potential for pollution. Therefore, it needs to be processed into beneficial products such as organic fertiliser to support sustainable agriculture. This programme aimed to provide education and training on the production of vermicompost, thereby increasing public knowledge on managing oil palm EFB waste in an environmentally friendly and economically valuable way. The implementation methods included dissemination of information on vermicomposting, technical training and mentoring, and evaluation through pre- and post-tests. The training involved 25 participants. The results of the community engagement activity demonstrated a significant increase in participants’ knowledge regarding the use of palm fronds. Evaluation showed a notable improvement in understanding, application, and programme impact, with scores rising from an average of 38.96% in the pre-test to 100% in the post-test. Overall, this activity enhanced the awareness of Kampung Sialang Sakti residents regarding the transformation of EFB waste into vermicompost by 62.04%, from 38.96% to 100%.